Carbon sequestration enhanced multi-source solid waste core-shell aggregate and preparation method thereof
Patent Information
- Application Number
- CN202611116769.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-30
AI Technical Summary
1、单纯物理包裹,源头危害未除:仅用水泥浆等胶凝材料包裹固废颗粒,固废本身含有的可溶性磷、氟、重金属等有害物质未被稳定化,在长期服役中仍会缓慢溶出,对混凝土基体和环境构成隐患
(1)本发明提供了一种固碳增强型多源固废核壳骨料,通过四层结构设计与工艺优化,解决现有技术中固废解毒不彻底、功能单一、层间结合薄弱的问题;通过功能化活化液的化学固定与原位诱导晶须生长,将固废中可溶磷、氟及重金属的浸出毒性降低90%以上,同时核心层抗压强度因晶须网络增强而提升30~50%,从根源上解决了固废骨料长期服役的环境与力学安全隐患。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, specifically relating to a carbon-enhanced multi-source solid waste core-shell aggregate and its preparation method. Background Technology
[0002] Concrete is the most widely used man-made building material in the world today. The depletion of its raw material, natural sand and gravel resources, and the pollution caused by the stockpiling of large quantities of industrial solid waste (such as steel slag, phosphogypsum, and lithium slag) present a sharp contradiction. Utilizing solid waste to prepare artificial aggregates is an important way to resolve this contradiction. However, existing solid waste-based aggregate technologies generally suffer from the following bottlenecks: 1. Simple physical wrapping does not eliminate the source of harm: Simply wrapping solid waste particles with cement slurry or other cementing materials does not stabilize the soluble phosphorus, fluorine, heavy metals and other harmful substances contained in the solid waste itself. These substances will still slowly dissolve during long-term service, posing a hidden danger to the concrete matrix and the environment.
[0003] 2. Limited functionality and lack of synergy: Existing technologies either focus only on strength or only on the solidification of a single pollutant (such as chloride ions), and cannot cope with the complex deterioration problems caused by multiple factors (chloride salt corrosion, heavy metal leaching, ammonia nitrogen pollution, radioactive radiation and shrinkage cracking) coexisting in harsh environments.
[0004] 3. Weak interlayer bonding and easy structural failure: If multi-layer functional aggregates lack a dense interface transition design, different functional layers are prone to delamination under stress and penetration, resulting in premature loss of function.
[0005] Currently, there are stricter standards for the environmental performance of concrete. Strict limits have been set for the leaching concentrations of radioactive nuclides, ammonia release, especially hexavalent chromium, water-soluble chloride ions, and various heavy metal ions. This requires building materials to not only have good mechanical properties but also long-term, reliable environmental safety. Existing technologies that simply crush solid waste as aggregate or grind it as admixture cannot fundamentally isolate or stabilize harmful components in solid waste, and cannot guarantee long-term compliance with environmental standards under complex service environments. This constitutes a technical barrier to entering the green building materials market.
[0006] Therefore, there is an urgent need to develop a multifunctional integrated material that can simultaneously achieve high-value utilization of solid waste, improve concrete durability, and proactively control environmental risks. The design concept of "core-shell structure" aggregate provides a new approach to solving these problems. This structure encapsulates the solid waste "core" with a dense, high-performance "outer shell," aiming to physically isolate the migration of harmful substances and optimize the interface between aggregate and cement paste. Summary of the Invention
[0007] The technical problem to be solved by this invention is to provide a carbon-fixed reinforced multi-source solid waste core-shell aggregate and its preparation method to address the shortcomings of existing technologies. Through systematic innovations of "source chemical fixation and in-situ self-reinforcement", "four-layer gradient multi-functional integration" and "dense interface transition + inner curing shell", it achieves efficient stabilization of harmful substances in solid waste, synergistic control of multiple pollutants, significant enhancement of interlayer bonding force, and effective inhibition of concrete shrinkage cracking, thereby obtaining a high-performance artificial aggregate with excellent long-term service safety and environmental compatibility.
[0008] To achieve the above objectives, according to one aspect of the present invention, a carbon-enhanced multi-source solid waste core-shell aggregate is provided, comprising, from the inside out, an activated and stable core layer, a composite functional layer, and an inner curing outer shell layer: The activated and stabilized core layer is formed by treating and solidifying a core mixture of steel slag powder, phosphogypsum powder, lithium slag powder, and silicate cement clinker with a functionalized activation liquid. The functionalized activation liquid contains metal salt additives capable of chemically fixing soluble harmful impurities in the core mixture, and nano-silica sol for inducing in-situ reinforcement. This reaction allows the soluble impurities to be converted into insoluble stable substances in the early stages of granulation, thus eliminating their environmental risks at the source. Simultaneously, under specific subsequent curing processes, specific components in the activation liquid can induce in-situ generation of reinforced structures within the core layer, achieving deep stabilization and endogenous reinforcement of solid waste. The composite functional layer is composed of cement clinker and functional materials. The functional materials are selected from at least one of chloride ion solidification materials, heavy metal reduction and stabilization materials, ammonia nitrogen fixation materials, and radioactive shielding and adsorption materials, depending on the target pollutant to be removed. The functional materials enable customized, efficient and synergistic control of different corrosive pollutants. The inner curing outer shell layer is set on the outermost layer of the core-shell aggregate and contains an inner curing agent; this layer forms a micro "reservoir" inside the concrete, which promotes the hydration of the surrounding cementitious materials by continuously releasing water, thereby inhibiting the shrinkage and cracking of the concrete. The core-shell aggregate also includes a dense interface transition layer, which is disposed between the activated and stable core layer and the composite functional layer or between the composite functional layer and the inner protective shell layer. This dense interface transition layer is used to enhance interlayer bonding and block the penetration of corrosive media. The dense interface transition layer is designed to overcome the common interface delamination problem between multi-layer structures. This layer can effectively isolate the penetration of external corrosive media along the interface and significantly enhance the bonding force between adjacent layers, ensuring the structural integrity of the core-shell aggregate during long-term service.
[0009] In the above scheme, by mass percentage, the activated and stable core layer accounts for 60% to 80%, the composite functional layer accounts for 15% to 50%, the dense interface transition layer accounts for 1% to 3%, and the inner protective outer shell layer accounts for 1% to 5%.
[0010] In the above scheme, the particle size of the carbon-enhanced multi-source solid waste core-shell aggregate is 3~35mm.
[0011] In the above scheme, in the activated and stabilized core layer, the mass ratio of the core mixed powder to the functionalized activation liquid is (8~10):1.
[0012] In the above scheme, the specific surface area of each raw material in the core mixed powder is ≥400 m². 2 / kg, to ensure reactivity.
[0013] In the above scheme, the mass ratio of steel slag powder, phosphogypsum powder, lithium slag powder and silicate cement clinker in the core mixed powder is (20~40):(30~40):(10~20):(30~60).
[0014] In the above scheme, the metal salt additives in the functionalized activation solution are selected from at least one of aluminum salts, phosphates, and soluble barium salts; the water-to-solid ratio of the functionalized activation solution is (3~10):1. During the subsequent steam curing process, the nano-silica sol and the metal salt additives work together to induce the in-situ generation of micron-level reinforcing structures in the core mixed powder, playing a dual role of endogenous reinforcement and deep stabilization of residual heavy metals.
[0015] In the above scheme, the ratio of the total mass of the functional materials to the mass of cement clinker in the composite functional layer is (2~4):(6~8) to ensure the effectiveness and density of the functional layer. When multiple functional materials are included, the proportion between the functions of each material can be adjusted according to the target pollutant concentration.
[0016] In the above scheme, the chloride ion curing material includes hydrotalcite powder and zeolite powder, and the mass ratio of hydrotalcite powder to zeolite powder is (0.5~2):1.
[0017] In the above scheme, the heavy metal reduction stabilizing material includes ferrous sulfide and calcium polysulfide, and the mass ratio of ferrous sulfide to calcium polysulfide is (0.5~2):1.
[0018] In the above scheme, the ammonia nitrogen fixation material includes clinoptilolite and magnesium phosphate, and the mass ratio of clinoptilolite to magnesium phosphate is (0.5~2):1.
[0019] In the above scheme, the radioactive shielding and adsorption material includes barite powder and titanium silicate, and the mass ratio of barite powder to titanium silicate is (0.5~2):1.
[0020] In the above scheme, the material of the dense interface transition layer is an aqueous solution of water glass modified silica sol or organosilane coupling agent; the water-to-solid ratio of the material of the dense interface transition layer is (3~10):1, so as to facilitate the formation of a uniform and dense film on the particle surface. The organosilane coupling agent is KH-550 or KH-560; The preparation method of the water glass modified silica sol is as follows: nano-silica is added to a water glass solution and ultrasonically dispersed for 5-10 minutes to obtain the water glass modified silica sol; wherein the mass ratio of nano-silica to the water glass solution is (0.1-0.5):1, the modulus of sodium silicate in the water glass solution is 2.2-3.4, and the concentration of the water glass solution is 20-30°Bé. In this invention, sodium ions in water glass are used to modify the active hydroxyl groups on the silicon surface, causing them to undergo a cross-linking reaction, and finally forming a denser and more adhesive film upon solidification.
[0021] In the above scheme, the inner protective outer shell layer is formed by mixing a cementitious material with an inner protective agent; The cementitious material is silicate cement clinker; the mass ratio of the silicate cement clinker to the internal curing agent is (7~9):(1~3); The internal curing agent is at least one of expanded perlite powder, polyacrylamide, or porous ceramic microspheres to ensure stable and long-lasting water release function.
[0022] This invention also provides a method for preparing the aforementioned carbon-enhanced multi-source solid waste core-shell aggregate, comprising the following steps: S1. Mix the raw materials of the core mixed powder in proportion to obtain the core mixed powder; prepare a functionalized activating solution containing metal salt additives and nano silica sol; S2. The functionalized activating liquid is mixed with the core mixed powder and granulated, and then cured to obtain activated and stable core particles as the activated and stable core layer; S3. The material of the composite functional layer or the material of the dense interface transition layer is wrapped around the surface of the activated and stable core particles; when the material of the composite functional layer is wrapped around the surface of the activated and stable core particles to form a composite functional layer, the material of the dense interface transition layer is then wrapped around the surface of the composite functional layer and cured to form a dense interface transition layer; when the material of the dense interface transition layer is wrapped around the surface of the activated and stable core particles and cured to form a dense interface transition layer, the material of the composite functional layer is then wrapped around the surface of the dense interface transition layer to form a composite functional layer; wherein the material of the composite functional layer is obtained by mixing functional materials and cement clinker in a certain proportion; S4. The outermost layer of the particles obtained in step S3 is wrapped with an inner curing shell material containing an inner curing agent to form an inner curing shell layer. After curing, the carbon-reinforced multi-source solid waste core-shell aggregate is obtained.
[0023] In the above scheme, spray granulation process is adopted in step S2, and the curing is steam curing with a curing temperature of 60~95℃ and a curing time of 4~12h; in steps S3 and S4, each layer of coating is carried out in a disc granulator, and each layer is dried or surface cured after coating before the next layer is coated to ensure clear interlayer interfaces and strong bonding; the surface curing treatment is conventional curing or steam curing.
[0024] In this invention, a functionalized activating liquid is used for the first time to chemically fix the core of solid waste (core mixed powder) at the source during the granulation stage, directly converting harmful substances into an insoluble state, achieving true "detoxification" and stabilization, and transforming the mechanism from "passive encapsulation" to "active modification".
[0025] In this invention, instead of directly adding finished whiskers, the functional activating liquid and solid waste components (core mixed powder) are reacted in situ under curing conditions to spontaneously generate a phosphogypsum whisker reinforcement network inside the aggregate core layer. This discovery enables the reinforcement and secondary stabilization effects to be achieved without additional processes and raw materials, realizing a process innovation from "external whisker addition" to "in situ growth".
[0026] In summary, compared with the prior art, the above-described technical solutions conceived by this invention can achieve the following beneficial effects: (1) This invention provides a carbon-enhanced multi-source solid waste core-shell aggregate. Through a four-layer structure design and process optimization, it solves the problems of incomplete solid waste detoxification, single function, and weak interlayer bonding in the existing technology. Through the chemical fixation of functionalized activating liquid and in-situ induced whisker growth, the leaching toxicity of soluble phosphorus, fluorine and heavy metals in solid waste is reduced by more than 90%. At the same time, the compressive strength of the core layer is increased by 30-50% due to the enhancement of the whisker network, which fundamentally solves the environmental and mechanical safety hazards of long-term service of solid waste aggregate.
[0027] (2) Through the customized design of the composite functional layer, the aggregate can simultaneously or separately efficiently solidify chloride ions (solidification rate ≥80%), reduce and stabilize heavy metals (leaching concentration lower than the national standard limit), fix ammonia nitrogen and shield and adsorb radioactive nuclides; multiple functions are integrated into one aggregate unit, which significantly extends the durability of concrete in harsh environments such as saline soil and industrial polluted sites.
[0028] (3) The outermost inner curing shell of the present invention forms a micro "reservoir" inside the concrete, continuously releasing water to promote the hydration of cementitious materials, which can reduce the self-shrinkage and drying shrinkage rate of concrete by more than 40%, effectively inhibiting the generation of cracks.
[0029] (4) The dense interface transition layer of the present invention effectively solves the problem of interface delamination between multi-layer structures, isolates the penetration of external corrosive media along the interface, significantly enhances the interlayer bonding force, and ensures the structural integrity of aggregates under complex stress and erosion environments.
[0030] (5) The core layer of this invention uses all industrial solid waste as raw material, without the need for high-temperature sintering, and the preparation process has low energy consumption; the in-situ self-reinforcing mechanism saves the cost and process of adding expensive reinforcing materials, and truly realizes the low-carbon circular goal of "treating waste with waste and turning waste into treasure". Detailed Implementation
[0031] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. Furthermore, the technical features involved in the various embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0032] It should be understood that the sequence number of each step in the embodiment does not imply the order of execution. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.
[0033] The raw materials used in the examples and comparative examples are as follows: The cement clinker used is silicate cement clinker, and the specific surface area of powders such as steel slag powder, phosphogypsum powder, and lithium slag powder is 420~450 m². 2 / kg, using materials such as hydrotalcite powder, zeolite powder, expanded perlite powder, and barite powder, with a specific surface area of 450~550 m². 2 / kg, all are commercially available products; The raw materials used, such as ferrous sulfide, calcium polysulfide, sodium aluminate, sodium dihydrogen phosphate, and sodium titanate, are all commercially available products. The method for preparing water glass modified silica sol is as follows: nano-silica is added to a water glass solution and ultrasonically dispersed for 10 minutes; the mass ratio of nano-silica to water glass solution is 0.1:1; the water glass solution used is a commercially available product with a modulus of 3.0 and a concentration of 20°Bé; the nano-silica is a commercially available product with a purity greater than 99.0% and a specific surface area of 400 m². 2 / g, with a particle size of 7~40 nm.
[0034] The organosilane coupling agent used is industrial grade KH-560.
[0035] The porous ceramic microspheres used have a median particle size of 10μm and a water absorption rate of 60%. They were wetted for 24 hours before use and were purchased from Shandong Okrola New Material Technology Co., Ltd.
[0036] Example 1 This embodiment prepares a core-shell aggregate for marine and de-icing salt environments, with chloride ion solidification as its core function; the preparation method of a carbon-enhanced multi-source solid waste core-shell aggregate provided in this embodiment is as follows: S1. Formulation of core mixed powder: Steel slag powder, phosphogypsum powder, lithium slag powder, and silicate cement clinker were weighed out in a mass ratio of 35:35:15:50. The specific surface area of each component was 420~450 m². 2 / kg, dry mix in a mixer for 10 minutes until uniform to obtain core mixed powder.
[0037] S2. Preparation of functionalized activating solution: Sodium aluminate and sodium dihydrogen phosphate were mixed in a 1:1 mass ratio to form a metal salt additive, accounting for 5% of the total mass of the functionalized activation solution; at the same time, nano silica sol with a solid content of 30% (average particle size of 15nm) was added, accounting for 50% of the total mass of the functionalized activation solution; the remainder was water. The mixture was stirred and dissolved thoroughly to obtain the functionalized activation solution, with the water-to-solid ratio controlled at 4:1.
[0038] S3. Preparation of activated and stabilized core particles: A spray granulation process is used to uniformly spray the functionalized activating liquid from step S2 into the core mixed powder from step S1, wherein the mass ratio of the core mixed powder to the functionalized activating liquid is 8:1, and granulation is performed to a particle size of 3-5 mm. The resulting particles are placed in a steam curing chamber and cured at 85°C for 8 hours to obtain activated and stable core particles as the activated and stable core layer.
[0039] During this process, the aluminates and phosphates in the activation solution undergo a chemical fixation reaction with the soluble phosphorus, fluorine, and some heavy metal ions dissolved in the phosphogypsum, generating insoluble calcium phosphate and aluminum-fluorine complexes. Simultaneously, the nano-silica sol induces the calcium sulfate component in the phosphogypsum to spontaneously grow in situ into micron-sized phosphogypsum whiskers with an aspect ratio of 10-30, forming a three-dimensional interwoven reinforcing network within the core layer.
[0040] S4. Wrapping of composite functional layers: Silicate cement clinker and chloride ion-curing functional material (hydrotalcite powder: zeolite powder = 1.5:1) were compounded at a mass ratio of 7:3 to obtain a composite functional layer mixture. The core particles from step S3 were placed in a disc granulator, and while rotating and spraying water, the above composite functional layer mixture was spread to coat the particles to a thickness of about 1 mm. The resulting particles were then placed in a steam curing chamber and cured at 85°C for 8 hours. The composite functional layer accounted for 30% of the total mass of the core and shell aggregate.
[0041] S5. Application of a dense interface transition layer: Prepare a water glass modified silica sol solution (water-to-solid ratio 5:1), spray it onto the surface of the particles obtained in step S4 to form a uniform thin film, and dry it with hot air at 50°C until the surface is cured to form a dense interface transition layer. The dense interface transition layer accounts for 1% of the total mass of the core-shell aggregate.
[0042] S6. Inner protective outer shell layer encapsulation: Silicate cement clinker and pre-wetted porous ceramic microspheres are mixed at a mass ratio of 8:2 to obtain an inner-cured outer shell mixture. The particles obtained in step S5 are then further coated to form an inner-cured outer shell layer, until the inner-cured outer shell layer accounts for 5% of the total mass of the core-shell aggregate. After coating, the mixture is cured by spraying water at room temperature for 24 hours to obtain the chloride ion-cured core-shell aggregate product.
[0043] Example 2 This embodiment prepares a core-shell aggregate for industrial contaminated sites and tailings ponds, with the core function of reducing and stabilizing heavy metals.
[0044] The preparation steps in this embodiment are the same as in Example 1, except that: S4. Composite functional layer wrapping: The functional material is replaced with ferrous sulfide and calcium polysulfide (mass ratio 1:1), and the total mass of the functional material is kept in the mass ratio of silicate cement clinker to 3:7.
[0045] S6. Inner protective outer shell layer: The inner protective agent is replaced with expanded perlite powder, with the same dosage.
[0046] Example 3 This embodiment prepares a core-shell aggregate with shielding and adsorption of radionuclides as its core function for nuclear facility decommissioning and radioactive waste disposal scenarios.
[0047] The preparation steps in this embodiment are the same as in Example 1, except that: S4. Composite functional layer wrapping: The functional materials are replaced with barite powder and sodium titanate (mass ratio 1.2:1), and the total mass of the functional materials is kept in the mass ratio of silicate cement clinker to 3:7.
[0048] Comparative Example 1 This comparative example is similar to Example 1, except that it lacks a functionalized activating solution (no source chemical fixation and in-situ self-reinforcement). This comparative example uses ordinary tap water instead of the functionalized activation solution. The water does not contain aluminum salts, phosphates, soluble barium salts, or nano-silica sol. The same core mixing powder ratio and curing regime as in Example 1 are used, and the remaining coating steps are the same as in Example 1.
[0049] Comparative Example 2 This comparative example does not have a four-layer structure (single-layer hybrid): This comparative example refers to Example 1, except that the layered encapsulation design of the composite functional layer, dense interface transition layer, and inner curing outer shell layer is omitted. All materials of the activated and stable core layer, composite functional layer, dense interface transition layer, and inner curing outer shell layer in Example 1 are mixed and granulated at one time, and steam-cured at 85°C for 8 hours to obtain homogeneous aggregate.
[0050] Comparative Example 3 Comparative Example 3: No inner protective outer shell layer: This comparative example prepares aggregate according to steps S1 to S5 of Example 1, but does not perform the inner curing outer shell layer coating in step S6.
[0051] Performance testing and application scenario evaluation The chloride ion curing rate, hexavalent chromium ion leaching concentration, sample shrinkage rate, and cylinder compressive strength of the aggregates obtained in the above embodiments and comparative examples were tested.
[0052] Table 1 Test results of each sample
[0053] ("—" indicates that this project has not tested this group; "Not Applicable" indicates that there is no corresponding structure for this group and it cannot be tested.) As shown in Table 1, the chloride ion curing rate of Example 1 reached 85%, which is 77% higher than that of Comparative Example 1 (without activation liquid) and 37% higher than that of Comparative Example 2 (without four-layer structure). This significant improvement stems from the enrichment effect of the composite functional layer and the synergistic effect of the activated and stable core layer in the four-layer structure of this invention—the core layer is pre-densified, making it more difficult for chloride ions to penetrate, thus being efficiently intercepted and cured in the outer functional layer; the Cr of Example 2 6+The leaching concentration was only 0.08 mg / L, a reduction of approximately 95% compared to Comparative Example 1. This indicates the dual stabilization mechanism of the present invention—the source chemical fixation of the functionalized activating liquid in the core layer (generating insoluble phosphate precipitates), and the reduction precipitation effect of ferrous sulfide / calcium polysulfide in the composite functional layer. Even if the aggregate cracks and breaks due to overload, the internal heavy metals still exist in an insoluble state, preventing secondary pollution. This is a "self-immune" function that cannot be achieved by simple physical encapsulation (Comparative Example 1). The 180-day shrinkage rate of concrete mixed with the aggregate of Example 1 was reduced by approximately 45% compared to concrete mixed with the aggregate of Comparative Example 3. This indicates that the outermost pre-wetted porous ceramic microspheres continuously release water as the internal humidity of the concrete decreases, maintaining the moisture environment required for the hydration of the cementitious material and reducing the self-shrinkage driving force from the root. This effect is completely absent in aggregates lacking an inner curing outer shell layer.
[0054] In summary, this invention, through systematic innovations such as "functionalized activation liquid source chemical fixation and in-situ self-reinforcement", "four-layer gradient multifunctional integration" and "dense interface transition + inner curing shell", enables the prepared core-shell aggregate to achieve good synergistic effects in chloride ion curing, long-term heavy metal stability, inhibition of shrinkage cracking and its own strength. Moreover, various properties can be customized according to engineering scenarios, making it particularly suitable for high-performance concrete structures in harsh environments such as marine engineering, industrial contaminated sites, and nuclear facility decommissioning.
[0055] It should be noted that, depending on the implementation needs, the various steps described in this application can be broken down into more steps, or two or more steps or parts of the steps can be combined into new steps to achieve the purpose of this invention.
[0056] Those skilled in the art will readily understand that the above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A carbon-fixing reinforced multi-source solid waste core-shell aggregate, characterized in that, It has an activation and stabilization core layer, a composite functional layer, and an inner maintenance outer shell layer that are sequentially wrapped from the inside out; The activated and stable core layer is formed by treating and solidifying a core mixture of steel slag powder, phosphogypsum powder, lithium slag powder and silicate cement clinker with a functionalized activation liquid. The functionalized activation liquid contains metal salt additives and nano-silica sol. The composite functional layer is composed of cement clinker and functional materials. The functional materials are selected from at least one of chloride ion solidification materials, heavy metal reduction and stabilization materials, ammonia nitrogen fixation materials, and radioactive shielding and adsorption materials, depending on the target pollutant to be removed. The inner curing outer shell layer is disposed on the outermost layer of the core-shell aggregate and contains an inner curing agent; The core-shell aggregate further includes a dense interface transition layer, which is disposed between the activated and stable core layer and the composite functional layer or between the composite functional layer and the inner curing outer shell layer.
2. The carbon-enhanced multi-source solid waste core-shell aggregate according to claim 1, characterized in that, By mass percentage, the activated and stable core layer accounts for 60% to 80%, the composite functional layer accounts for 15% to 50%, the dense interface transition layer accounts for 1% to 3%, and the inner protective outer shell layer accounts for 1% to 5%. The particle size of the carbon-enhanced multi-source solid waste core-shell aggregate is 3~35mm.
3. The carbon-enhanced multi-source solid waste core-shell aggregate according to claim 1, characterized in that, In the activated and stabilized core layer, the mass ratio of the core mixed powder to the functionalized activation liquid is (8~10):
1.
4. The carbon-enhanced multi-source solid waste core-shell aggregate according to claim 1, characterized in that, The mass ratio of steel slag powder, phosphogypsum powder, lithium slag powder and silicate cement clinker in the core mixed powder is (20~40):(30~40):(10~20):(30~60); The specific surface area of each raw material in the core mixed powder is ≥400 m². 2 / kg.
5. The carbon-enhanced multi-source solid waste core-shell aggregate according to claim 1, characterized in that, The metal salt additives in the functionalized activating solution are selected from at least one of aluminum salts, phosphates, and soluble barium salts; the water-to-solid ratio of the functionalized activating solution is (3~10):
1.
6. The carbon-enhanced multi-source solid waste core-shell aggregate according to claim 1, characterized in that, In the composite functional layer, the total mass ratio of the functional materials to the cement clinker is (2~4):(6~8); The chloride ion curing material includes hydrotalcite powder and zeolite powder, and the mass ratio of hydrotalcite powder to zeolite powder is (0.5~2):1; The heavy metal reduction stabilizing material includes ferrous sulfide and calcium polysulfide, wherein the mass ratio of ferrous sulfide to calcium polysulfide is (0.5~2):1; The ammonia nitrogen fixation material includes clinoptilolite and magnesium phosphate, and the mass ratio of clinoptilolite to magnesium phosphate is (0.5~2):1; The radioactive shielding and adsorption material comprises barite powder and titanium silicate, wherein the mass ratio of barite powder to titanium silicate is (0.5~2):
1.
7. The carbon-enhanced multi-source solid waste core-shell aggregate according to claim 1, characterized in that, The material of the dense interface transition layer is an aqueous solution of water glass modified silica sol or organosilane coupling agent; the water-to-solid ratio of the material of the dense interface transition layer is (3~10):
1. The organosilane coupling agent is KH-550 or KH-560; The method for preparing the water glass modified silica sol is as follows: nano-silica is added to a water glass solution and ultrasonically dispersed for 5-10 minutes to obtain the water glass modified silica sol; wherein the mass ratio of nano-silica to the water glass solution is (0.1-0.5):1, the modulus of sodium silicate in the water glass solution is 2.2-3.4, and the concentration of the water glass solution is 20-30°Bé.
8. The carbon-enhanced multi-source solid waste core-shell aggregate according to claim 1, characterized in that, The inner curing outer shell layer is formed by mixing a cementitious material with an inner curing agent; The cementitious material is silicate cement clinker; the mass ratio of the silicate cement clinker to the internal curing agent is (7~9):(1~3); The internal curing agent is at least one of expanded perlite powder, polyacrylamide, or porous ceramic microspheres.
9. A method for preparing carbon-enhanced multi-source solid waste core-shell aggregate as described in any one of claims 1 to 8, characterized in that, Includes the following steps: S1. Mix the raw materials of the core mixed powder in proportion to obtain the core mixed powder; prepare a functionalized activating solution containing metal salt additives and nano silica sol; S2. The functionalized activating liquid is mixed with the core mixed powder and granulated, and then cured to obtain activated and stable core particles as the activated and stable core layer; S3. The material of the composite functional layer or the material of the dense interface transition layer is wrapped around the surface of the activated and stable core particles; when the material of the composite functional layer is wrapped around the surface of the activated and stable core particles to form a composite functional layer, the material of the dense interface transition layer is then wrapped around the surface of the composite functional layer and cured to form a dense interface transition layer; when the material of the dense interface transition layer is wrapped around the surface of the activated and stable core particles and cured to form a dense interface transition layer, the material of the composite functional layer is then wrapped around the surface of the dense interface transition layer to form a composite functional layer; wherein the material of the composite functional layer is obtained by mixing functional materials and cement clinker in a certain proportion; S4. The outermost layer of the particles obtained in step S3 is wrapped with an inner curing shell material containing an inner curing agent to form an inner curing shell layer. After curing, the carbon-reinforced multi-source solid waste core-shell aggregate is obtained.
10. The method for preparing carbon-enhanced multi-source solid waste core-shell aggregate according to claim 9, characterized in that, In step S2, a spray granulation process is used, and the curing is steam curing at a temperature of 60~95℃ for 4~12 hours. In steps S3 and S4, each layer of coating is carried out in a granulator, and each layer is dried or surface cured after coating. The surface curing treatment is either conventional curing or steam curing.